Kontribusi Mediator Nonhakim dalam Penyelesaian Konflik Rumah Tangga - Darmawan, Aldy Darmawan; Elfia, Elfia; Zulfan, Zulfan (Institut Agama Islam Negeri Kerinci, 2023)
The success rate of mediation conducted by non-judge mediators at the Class 1A Religious Court in Padang is higher than that of mediation conducted by judges. In 2022, out of 54 cases successfully mediated, 17 were mediated by judges, while 37 were mediated by non-judge mediators. This article aims to explain how non-judge mediators contribute to case mediation. Using interview techniques and document studies, this research reveals that the presence of non-judge mediators has provided an alternative mediation model in the Religious Court amidst the generally low national success rate of mediation in religious courts. As a result, the success rate of mediation has continuously increased year by year at the Class 1A Religious Court in Padang, with the highest success rate among non-judge mediators. During the mediation process, non-judge mediators focus more on providing advice and counsel on psychological aspects rather than rational aspects, allowing the reasons for divorce presented in the parties' petitions to be considered with feelings and conscience rather than purely rational thoughts that tend to push them towards divorce.